2016
DOI: 10.1002/adfm.201670029
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modifications: Interactions between an Aryl Thioacetate‐Functionalized Zn(II) Porphyrin and Graphene Oxide (Adv. Funct. Mater. 5/2016)

Abstract: Design and synthesis of a novel porphyrin‐based nanohybrid, whereby the entire surface of GO is modified via supramolecular assembly, is reported by S. I. Pascu and co‐workers on page 687. The Zn(II)‐porphyrin@GO nanohybrid forms stable dispersions in ethanol, likely containing free and bound Zn(II)‐porphyrin in a dynamic exchange. New opportunities for using uniform dispersions of tailor‐made nanohybrids incorporating GO within layered materials are opened up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It has already been shown that Zn‐porphyrins can be functionalised and their self‐assembly can generate nanorings of 5–60 porphyrin units . Earlier observations by AFM or STM measurements performed on drop‐casted solutions show that such supramolecular architectures can be described as nanocrystalline aggregates of porphyrins, having a shape of a ring or tower, with sizes varying in the range of hundreds of nanometers, depending on the imaging method used to evaluate the size …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has already been shown that Zn‐porphyrins can be functionalised and their self‐assembly can generate nanorings of 5–60 porphyrin units . Earlier observations by AFM or STM measurements performed on drop‐casted solutions show that such supramolecular architectures can be described as nanocrystalline aggregates of porphyrins, having a shape of a ring or tower, with sizes varying in the range of hundreds of nanometers, depending on the imaging method used to evaluate the size …”
Section: Resultsmentioning
confidence: 99%
“…We characterised these materials in a thin film environment using fluorescence lifetime measurements via time‐correlated single photon counting (TCSPC) combined with multi‐photon laser scanning confocal microscopy; this allows us to gain detailed information on the environment of the fluorophore upon immobilisation within the nanomaterial hybrid and estimate the influence of the different linking strategies on the emerging materials′ optical properties by observing their quenching characteristics in solution and in the solid state …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations